Feasibility of integrated, multilevel care for cardiovascular diseases (CVD) and HIV in low- and middle-income countries (LMICs): A scoping review. - Temitope Ojo; Lynette Lester; Juliet Iwelunmor; Joyce Gyamfi; Chisom Obiezu-Umeh; Deborah Onakomaiya; Angela Aifah; Shreya Nagendra; Jumoke Opeyemi; Mofetoluwa Oluwasanmi; Milena Dalton; Ucheoma Nwaozuru; et al. (PLoS ONE)
Background Integrated cardiovascular disease (CVD) and HIV (CVD-HIV) care interventions are being adopted to tackle the growing burden of noncommunicable diseases (NCDs) in low-and middle-income countries (LMICs) but there is a paucity of studies on the feasibility of these interventions in LMICs. This scoping review aims to present evidence of the feasibility of integrated CVD-HIV care in LMICs, and the alignment of feasibility reporting in LMICs with the existing implementation science methodology. Methods A systematic search of published articles including systematic and narrative reviews that reported on integrated CVD-HIV care was conducted, using multiple search engines including PubMed/Medline, Global Health, and Web of Science. We examined the articles for evidence of feasibility reporting. Adopting the definition of Proctor and colleagues (2011), feasibility was defined as the extent to which an intervention was plausible in a given agency or setting. Evidence from the articles was synthesized by level of integration, the chronic care continuum, and stages of intervention development. Results Twenty studies, reported in 18 articles and 3 conferences abstracts, reported on feasibility of integrated CVD-HIV care interventions. These studies were conducted in Sub-Saharan Africa, Southeast Asia and South America. Four of these studies were conducted as feasibility studies. Eighty percent of the studies reported feasibility, using descriptive sentences that included words synonymous with feasibility terminologies in existing definition recommended by Proctor and colleagues. There was also an overlap in the use of descriptive phrases for feasibility amongst the selected studies. Conclusions Integrating CVD and HIV care is feasible in LMICs, although methodology for reporting feasibility is inconsistent. Assessing feasibility based on settings and integration goals will provide a unique perspective of the implementation landscape in LMICs. There is a need for consistency in measures in order to accurately assess the feasibility of integrated CVD-HIV care in LMICs.